Methods for Controlling Gas Turbine Casing Flows During Engine Shutdown - Andrew Pilkington; Budimir Rosic; Shigenari Horie (International Journal of Turbomachinery, Propulsion and Power, 2018)
During the shutdown of a gas turbine, natural convection flows occur inside of the engine casing. These natural convection flows cause the top of the engine casing to cool more slowly than the bottom of the casing. This non-uniform cooling can cause the casing to distort, known as “cat-back” distortion. This distortion leads to reduced tip and seal clearances, which can cause rubbing and binding. In this study, two different methods for reducing the non-uniform casing heat transfer in an industrial gas turbine during shutdown were investigated. A baseline case with no active method for reducing the casing heat transfer was compared with purge and flow extraction methods. It was found that the new proposed extraction method improved the uniformity of the casing heat transfer during the initial shutdown period.